KINERJA BETON SELF-HEALING BERBASIS ENKAPSULASI UNTUK APLIKASI STRUKTUR JEMBATAN BETON - rechita aprinnisa; Luthfi Muhammad Mauludin; Gandhi Widiarnoko (Jurnal Jalan Jembatan, 2026)
This study investigates the performance of self-healing concrete incorporating Bacillus megaterium encapsulated in Polyvinyl Alcohol (PVA) microcapsules for potential applications in road and bridge structures. The study evaluates the effect of 2% PVA microcapsules on compressive strength and self-healing capability of concrete. Cylindrical specimens (150 × 300 mm) were tested at curing ages of 7 and 28 days in accordance with ASTM C39. The results showed that self-healing concrete exhibited higher compressive strength than normal concrete, reaching 25.46 MPa at 7 days and 32.13 MPa at 28 days, compared to 23.97 MPa and 28.48 MPa, respectively. After 28 days, damaged specimens were immersed in water to provide moisture conditions that support bacterial activation and biomineralisation during the self-healing process. The post-healing compressive strength reached 16.88 MPa, corresponding to approximately 53% recovery of the initial strength. The strength recovery is attributed to Microbially Induced Calcite Precipitation (MICP), in which bacterial activity promotes calcium carbonate (CaCO₃) precipitation that fills microcracks and pores within the concrete matrix. SEM and EDS analyses confirmed matrix densification and the presence of CaCO₃ deposits associated with bacterial biomineralization. The findings indicate that PVA-encapsulated Bacillus megaterium has a significant potential to improve the durability, crack-healing capability, and service life of concrete structures for road and bridge infrastructure applications   Kata Kunci: Bacillus megaterium, beton self-healing, polyvinyl alcohol (PVA), kuat tekan, kalsium karbonat. Keywords: Bacillus megaterium, self-healing concrete, polyvinyl alcohol (PVA), compressive strength, calcium carbonate.